Specific features of diagnosis of ankylosing spondylitis in the presence of uveitis in persons of different sex - A. P. Rebrov; A. V. Aparkina; A. I. Akulova; Inna Zurabievna Gaidukova (Современная ревматология)
In patients with ankylosing spondylitis (AS), uveitis is its most common extraarticular manifestation (it occurs in 20–40% of cases).Objective: to study the specific features of diagnosis of AS in the presence of uveitis in persons of different sex.Subjects and methods. The study included 94 patients with AS. The rate of uveitis, patient age at its first episode, in the clinical manifestations of AS (inflammatory dorsalgia, arthritis, and enthesis), and in making a diagnosis, as well as disease activity were estimated in patients of different sex in the presence and absence of uveitis.Results. Uveitis as an extraskeletal manifestation of AS was stablished to more common in women (40%) than in men (15.8%). In female patients, the presence of uveitis is associated with early-onset AS as compared to those without uveitis. At the same time the diagnosis of AS was made in the women with uveitis 7 years later than in those without this condition. In one fifth of the patients, uveitis occurred before or concurrently with the appearance of the symptoms of locomotive lesion.Conclusion. Uveitis is more common in women with AS than in men and associated with the late detection of locomotive pathology.